Captain Underpants and the revolting revenge of the Radioactive Robo-Boxers : the tenth epic novel - Pilkey, Dav, 1966- (New York : Scholastic, 2013)
After his time-traveling deeds cause the destruction of the world by preventing Harold and George from creating Captain Underpants, Tippy Tinkletrousers tries to use his time machine to correct the situation, but it proves to be difficult to fix.
5.3
3-6
890L
Keywords: Captain Underpants (Fictitious character) -- Juvenile fiction; Time travel -- Juvenile fiction; Bullying -- Juvenile fiction; Schools -- Juvenile fiction; Heroes -- Juvenile fiction; Captain Underpants (Fictitious character) -- Fiction; Time travel -- Fiction; Bullies -- Fiction; Schools -- Fiction; Heroes -- Fiction; Humorous stories; Cartoons and comics; School stories; Heroes and heroines -- Fiction; Humorous fiction; Comic books, strips, etc; Superheroes -- Fiction; Humorous fiction